Finite element analysis of the simulated mechanical stresses in molar occlusion in the pterygoid pillar of a human skull : Análise de elementos finitos das tensões mecânicas simuladas em oclusão molar no pilar pterigoideo de um crânio humano - Rolfini, Elisa Camila Santos, 1989- (2014)
Orientador: Felippe Bevilacqua Prado